Kajian Semiotik pada Poster Politik Calon Presiden dan Wakil Presiden 2024 di Ciayumajakuning - Mujtaba, Sultan Tirta; Itaristanti, Itaristanti; Nurpadillah, Veni; Sueb, Sueb (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2024)
The aim of this research is to describe the meaning of signifiers and signifieds on political posters for the 2024 presidential and vice presidential candidates in Ciayumajakuning. This type of research is qualitative. The data source for this research is 38 posters of 2024 presidential and vice presidential candidates spread across Ciayumajakuning. Data collection was carried out using documentation techniques, followed by listening and note-taking techniques. The advanced technique used is the skillful free-involved listening technique. Meanwhile, the instrument used in this research uses data cards. Meanwhile, the data analysis technique in this research uses translational equivalent and referential equivalent techniques. The results of this research obtained ten meanings. These meanings are: 1) prohibition on daydreaming and immediately taking real action; 2) program for the welfare of the Indonesian people, 3) invitation to vote; 4) hope to obtain sustenance more easily; 5) principles of state building; 6) support for candidate pairs; 7) ideas for advancing Indonesia; 8) readiness of potential leaders; 9) characteristics of potential leaders; and 10) advanced Indonesian leaders. With this research, it is hoped that the public can understand the meaning related to political posters for presidential and vice presidential candidates. AbstrakTujuan penelitian ini adalah untuk mendeskripsikan makna penanda dan petanda pada poster politik calon presiden dan wakil presiden 2024 di Ciayumajakuning. Jenis penelitian ini adalah kualitatif. Sumber data pada penelitian ini adalah 38 poster calon presiden dan wakil presiden 2024 yang tersebar di Ciayumajakuning. Pengumpulan data dilakukan dengan teknik dokumentasi, dilanjutkan dengan teknik simak dan catat. Teknik lanjutan yang digunakan adalah teknik simak bebas libat cakap. Sementara itu, teknik analisis data dalam penelitian ini menggunakan teknik padan translasional dan padan referensial. Hasil penelitian ini diperoleh sepuluh makna. Adapun makna-makna tersebut yaitu 1) larangan berangan-angan segera lakukan tindakan yang nyata; 2) program mensejahterakan rakyat Indonesia, 3) ajakan memilih; 4) harapan untuk mendapatkan rezeki dengan lebih mudah; 5) prinsip membangun negara; 6) dukungan kepada paslon; 7) gagasan memajukan Indonesia; 8) kesiapan calon pemimpin; 9) sifat calon pemimpin; dan 10) pemimpin Indonesia maju. Dengan adanya penelitian ini, diharapkan masyarakat dapat memahami makna terkait poster politik calon Presiden dan Wakil Presiden.